Women’s empowerment in agriculture, production diversity, and nutrition: Evidence from Nepal - Kadiyala, Suneetha; Quisumbing, Agnes R.; Cunningham, Kenda; Tyagi, Parul; Malapit, Hazel J. (International Food Policy Research Institute, 2013)
With the increasing recognition that agricultural growth and development do not necessarily translate into improved nutrition outcomes, policymakers are increasingly grappling with how to design and implement agricultural policies and programs that can also achieve nutritional objectives. Agriculture has direct links to nutrition in that it provides a source of food and nutrients and a broad-based source of income, as well as directly influencing food prices.